2012
DOI: 10.1016/j.jacc.2012.08.986
|View full text |Cite
|
Sign up to set email alerts
|

Effects of AMG 145 on Low-Density Lipoprotein Cholesterol Levels

Abstract: In phase 1 studies, AMG 145 significantly reduced serum LDL-C in healthy and hypercholesterolemic statin-treated subjects, including those with heterozygous familial hypercholesterolemia or taking the highest doses of atorvastatin or rosuvastatin, with an overall AE profile similar to placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
48
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 217 publications
(58 citation statements)
references
References 18 publications
10
48
0
Order By: Relevance
“…Mean unbound exposures and the observed relatively large variability in the healthy participants from this study were consistent with results from previously conducted single‐dose studies in healthy volunteers 17. Considerable overlap in the C max and AUC values was observed between healthy subjects and those with hepatic impairment (Figure 2).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Mean unbound exposures and the observed relatively large variability in the healthy participants from this study were consistent with results from previously conducted single‐dose studies in healthy volunteers 17. Considerable overlap in the C max and AUC values was observed between healthy subjects and those with hepatic impairment (Figure 2).…”
Section: Discussionsupporting
confidence: 90%
“…The timing and magnitude of LDL‐C lowering after a dose of evolocumab were consistent with those seen in other studies in patients and healthy volunteers 5, 6, 8, 17, 31. For example, the randomized, double‐blind, placebo‐controlled, phase 2 MENDEL study showed that monotherapy with evolocumab 140 mg Q2W in 45 patients with hypercholesterolemia (baseline LDL‐C 3.6 mmol/L) reduced LDL‐C from baseline by 51% (95% CI –56% to –46%) after 12 weeks of treatment 31.…”
Section: Discussionsupporting
confidence: 88%
“…15,20-24 The magnitude of the lowering of the LDL cholesterol level that we found with inclisiran was generally similar to that observed previously with anti-PCSK9 antibodies 20-24 or intensive statin therapy. 25 However, inclisiran differs mechanistically from anti-PCSK9 antibodies.…”
Section: Discussionsupporting
confidence: 89%
“…HDL levels in patients with PCSK9 mutations are generally increased[75-77] and most placebo-controlled trials of PCSK9 inhibitors have shown modest increases in HDL levels. [78-82] Furthermore, plasma levels of PCSK9 are associated with plasma apoM levels. [64]…”
Section: Discussionmentioning
confidence: 99%